Everything you need to launch and grow your new business (Boston, Massachusetts, 2018)
Starting an independent new business is rife with both opportunity and risk. From the basics of writing a business plan to the challenges of financing your new venture, the HBR Entrepreneur's Handbook is your essential resource for getting your startup off the ground. Topics include: Navigating the world of venture capital funding Turning innovations into successful realities in the marketplace Building a business model that makes sense for your business Developing the sales and marketing programs needed for your venture What entrepreneurial leaders must do to build culture and set direction.
Keywords: Kế hoạch kinh doanh,Business planning